Human Plasma Protein Adsorption onto Alumina Nanoparticles Relevant to Orthopedic Wear. Issue 2 (July 2015) - Gibbons, John P.; Monopoli, Marco P.; Lundqvist, Martin; Montes-Burgos, Iker; McGrath, Eilis E.; Elia, Giuliano; Lynch, Iseult; Dawson, Kenneth A.; Stanton, Kenneth T.
Purpose: Wear of ceramic orthopedic devices generates nanoparticles in vivo that may present a different biological character from the monolithic ceramic from which they are formed. The current work investigated protein adsorption from human plasma on alumina nanoparticles and monolithic samples representative of both wear particles and the ceramic components as implanted. Materials and Methods: A physicochemical characterization of the particles and their dispersion state was carried out, and the protein adsorption profiles were analyzed using 1D SDS-PAGE and mass spectrometry. Results: Significant differences in protein-binding profiles were identified where the nanoparticles selectively bound known transporter proteins rather than the more highly abundant serum proteins that were observed on the monoliths. Conclusions: Proteins associated with opsonization of particles were seen to be present in the protein corona of the nanoparticles, which raises questions regarding the role of wear particles in periprosthetic tissue inflammation and aseptic loosening.